Pengaruh Fluktuasi Harga, Kualitas Produk dan Kondisi Cuaca Terhadap Pendapatan Usaha Garam di Madura - Kamilah, Maslahatun; Nugroho, Prasetyo; Setyo Dwi Purnomo, Arie (Indonesian Journal of Islamic Economics and Business, 2024)
This study aims to analyze the impact of market price fluctuations, product quality, and weather conditions on salt business income in Madura. This study uses a quantitative approach with a multiple linear regression method to determine the influence between these variables. Primary data was obtained through direct surveys to salt farmers in Sumenep, while secondary data was obtained from the coordinator. The sample used in this study was 90 respondents, using the calculation of the solvin formula with a population of 880 farmers. The results of this study show that salt business income in Madura has a significant effect both partially and simultaneously by price fluctuations, product quality and weather conditions